Impact of Dental Caries and Odontogenic Infections on Henoch-Schönlein Purpura in Pediatric Patients - Yafeng Yang; Li Duan; Xiaoyan Ding; Xinghua Yang; Yuxin Yang; Ziang Zhao; Yanan Ma; Ruimin Li (International Dental Journal)
Objective: To investigate the impact of dental caries and odontogenic infections on pediatric patients with Henoch-Schönlein purpura (HSP), and to preliminarily explore the relationship between dental caries and the progression of HSP in these patients. Methods: From September 2021 to September 2022, 45 pediatric patients diagnosed with HSP at our hospital, were enrolled in this clinical study. The patients were divided into three groups: Group A (HSP without dental caries, n = 12), Group B (HSP with dental caries, n = 18), and Group C (HSP with dental caries receiving systematic treatment for dental caries, n = 15). Clinical indicators and the recurrence of HSP were monitored at a 3-month follow-up. Additionally, the 16S rDNA high-throughput sequencing technique was used to analyze changes in the composition and diversity of oral microbiota in the saliva and dental plaque of the patients. Results: Compared to discharge, Group B showed a significant increase in urinary protein (PRO) at the 3-month follow-up (P < .05), while Group C demonstrated a notable increase in red blood cell count (RBC) and hemoglobin (HGB), along with a significant decrease in red cell distribution width coefficient of variation (RDW-CV), monocyte count, and urinary white blood cell count (UWBC) (all P < .05). The oral microbiota composition across the three groups was largely similar. However, compared to HSP patients without dental caries, those with dental caries exhibited an increased abundance of Prevotella and Streptococcus mutans, along with a trend toward reduced oral microbiota diversity. After systematic treatment for dental caries, there was a significant increase in oral microbiota diversity as measured by the Shannon index (P < .05). Conclusions: Oral examinations and early systematic dental treatments for pediatric patients with HSP can enhance oral microbiome diversity, mitigate the impact of odontogenic foci on systemic health, and may help reduce the recurrence rate of HSP and the risk of nephritis complications.